HOW LEARNING FOREIGN LANGUAGES CAN HELP STUDENTS BE INTERCULTURAL COMPETENT? - Tursinbaeva , Dilbar Ixtiyar qizi (GOLDEN BRAIN, 2024)
This article examines the importance of learning different languages in order to be intercultural competent and develop socio skills.